Effect of Silver Nanoparticles on the Morphology of Toxoplasma gondii and Salmonella braenderup. (13th July 2020) - Vergara-Duque, Diego; Cifuentes-Yepes, Liliana; Hincapie-Riaño, Tatiana; Clavijo-Acosta, Felipe; Juez-Castillo, Graciela; Valencia-Vidal, Brayan
Abstract : The study of silver nanoparticles (AgNPs) has recently increased due to the different antimicrobial properties that have been evaluated. Studies have shown that AgNPs decrease the cell viability of some parasitic species and inhibit bacterial growth and biofilm formation. Toxoplasma gondii is a parasite with different stages of development including the oocyst, and it can survive in the environment for a long time generating contamination of vegetables and water. This parasite has the ability to generate congenital toxoplasmosis and chorioretinitis in humans. Another human pathogen present in water is Salmonella braenderup, this bacterium, when consumed, causes gastroenteritis and typhoid fever. We evaluate the affectation that causes the AgNPs in oocysts of T. gondii and S. braenderup using fluorescence microscopy and scanning electron microscopy techniques. The results showed that at different ratios of AgNPs and microorganisms, as well as at different exposure time during the treatments, morphological alteration of the cell structure of oocysts of T. gondii and S. braenderup was evidenced, suggesting a potential treatment method for the inhibition of the viability of these microorganisms.